2010
DOI: 10.1021/jp1000804
|View full text |Cite
|
Sign up to set email alerts
|

Hydrates of Cu2+ and CuCl+ in Dilute Aqueous Solution: A Density Functional Theory and Polarized Continuum Model Investigation

Abstract: In this work, structures, and properties of Cu(2+) and CuCl(+) hydrates in the gas and aqueous phases have been investigated using the B3LYP method. Contact ion pair (CIP) and solvent-shared ion pair (SSIP) were both taken into account for CuCl(+) hydrates. Our calculations show that [Cu(H(2)O)(n)](2+) clusters favor a very open four-coordinated structure for n = 5-12 in the gas phase, while a five-coordinated conformer is favored for n > or = 8 in the aqueous phase. An approximate complete solvation shell of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 42 publications
8
44
0
Order By: Relevance
“…However, the electronic interactions between the copper and coordinated waters must play a central role in governing the absolute orientations of the molecules in the structure. In fact, a gas-phase geometry optimization of an isolated CuSO 4 Á5H 2 O results in a totally planar arrangement of the coordinated water molecules (in agreement with some previous gas and solution-phase studies 7,14,16,30 ), demonstrating that the crystalline environment causes the observed tilting of the waters. Any structural deviations from the isolated-molecule calculation can be viewed as a strain, which results in a weakened copper-water bent bond, but this strain penalty must be offset by favorable cohesive interactions of the bulk solid for crystallization to occur.…”
Section: Orbital Analysissupporting
confidence: 89%
See 2 more Smart Citations
“…However, the electronic interactions between the copper and coordinated waters must play a central role in governing the absolute orientations of the molecules in the structure. In fact, a gas-phase geometry optimization of an isolated CuSO 4 Á5H 2 O results in a totally planar arrangement of the coordinated water molecules (in agreement with some previous gas and solution-phase studies 7,14,16,30 ), demonstrating that the crystalline environment causes the observed tilting of the waters. Any structural deviations from the isolated-molecule calculation can be viewed as a strain, which results in a weakened copper-water bent bond, but this strain penalty must be offset by favorable cohesive interactions of the bulk solid for crystallization to occur.…”
Section: Orbital Analysissupporting
confidence: 89%
“…[10][11][12][13] One such species is hexaaqua-copper(II), whose solvent phase structure has been a subject of controversy, specifically regarding the orientation of the coordinated water molecules. 7,9,[14][15][16][17] While not a direct probe of the solvated aqueous copper(II) cation, X-ray diffraction (XRD) studies of crystallized copper(II) hydrates can provide useful geometry information regarding the local environment around the metal cations with atomic precision. Investigation of crystalline solid-state samples enables rigorous study of both geometry and underlying electronic structure, leading to deeper understanding of their relationship.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hybrid DFT method, Becke's three-parameter exchange potential and Lee-Yang-Parr correlation functional (B3LYP) (Becke, 1993), for calculating the hydration of alkali mental halides and [CuCl x -(H 2 O) n ] 2Àx (x = 0-4) clusters, has shown a reasonable success (Lee et al, 2005;Olleta et al, 2006Olleta et al, , 2007Xia et al, 2009Xia et al, , 2010Xu et al, 2014;Yi et al, 2009Yi et al, , 2011 (Oolg et al, 1987) (RECPs), added a set of two f and one g polarization functions, used for Cu (jointly abbreviated here as aVDZ). 50% basis set superposition error (BSSE) correction was done (Kim et al, 2000).…”
Section: Dft Calculation Protocolsmentioning
confidence: 99%
“…So quantum mechanical calculations and molecular simulations for the Cu-Cl complexes in CuCl 2 -MCl (M = Na, Li)-H 2 O systems can be used to explain and predict experimental observations. A series of [CuCl x ] 2Àx (x = 0-4) hydration clusters have been studied through density functional theory (DFT) calculations (Xia et al, 2009(Xia et al, , 2010Yi et al, 2011) 8,10) clusters, in which one of three Cl À in the second or third complexing layer, are considered as solvent separated ion pair (1SSIP or 2SSIP) conformers of [CuCl 3 ] À aq species in the following context. Hydration energies and electronic absorption spectra are employed to analyze structural characteristics and UV-Vis spectra of CIP and 1SSIP/2SSIP conformers.…”
Section: Introductionmentioning
confidence: 99%